Efforts to Improve Civics Learning Outcomes Using the Active Learning Model of the Role Reversal Question Type for Grade V Elementary School Students - Afneda, Nazwa Resya (International Journal of Students Education, 2024)
The purpose of this study is that the results of learning PKn are still below the minimum completeness criteria for students because they still apply conventional learning models. Researchers will take action to overcome the problem by applying the active learning model of the role reversal question type which aims to find out whether the active learning model of the role reversal question type can improve the learning outcomes of PKn for grade V elementary school students. In reality, in the process of learning PKn in elementary schools, students are not fully involved directly, as is the case in grade V. Learning activities are still dominated by teacher activities, namely by using the lecture method when explaining the subject matter. This research method uses the literature review research method. The data collection techniques used are using tests, observation sheets and documentation. The data analysis technique used is completeness analysis to see student completeness and analysis of student activity observations from the results of pre-cycle learning, cycle I, cycle II and cycle III. The results of the study indicate that the use of the active learning model of the role reversal question type can improve the learning outcomes of PKn for elementary school students.